The temperature and size effect on the electrical resistivity of Cu/V multilayer films. (March 2017) - Wang, P.P.; Wang, X.J.; Du, J.L.; Ren, F.; Zhang, Y.; Zhang, X.; Fu, E.G.
Abstract: The electrical resistivity of sputter-deposited Cu/V multilayer films with different individual layer thicknesses varying from 2.5 to 100 nm was evaluated in the temperature range of 150–300 K. The temperature coefficient of resistivity (TCR) of Cu/V multilayer was compared based on the semi-classical theory of Dimmich model. A new model has been proposed to describe the relationship between the resistivity and the individual layer thickness of metallic multilayer film by considering both interface scattering and grain boundary scattering based on Fuchs-Sondheimer method and Mayadas-Shatzkes method. Graphical abstract: Image 1